Thrift Business Marketing Mix Strategy (Study at NS Thrift Store) in Pinrang District - Aslinda, Nur; Nuryamin, Muh; Jamaluddin, Jamaluddin; Khaeruddin, Faizah; Muis, Nurhasni (Jurnal Administrasi Bisnis, 2025)
Thrift Business Marketing Mix Strategy (Study on NS Thrift Store) in Pinrang Regency. Thesis for the Study Program of Business Administration, Department of Administrative Sciences, Faculty of Social Sciences and Law, Makassar State University. Supervised by Muh. Nur Yamin and Jamaluddin. This study aims to determine and analyze the right marketing mix strategy (Case Study NS Thrift Store) in Pinrang District. The research method used is a qualitative descriptive research approach using data collection methods through observation, interviews and documentation of research objects, which are then analyzed using SWOT analysis. Based on the results of the study, it shows that the strategy implemented by NS Thrift Store is in accordance with the SWOT analysis which is in quadrant I, namely an aggressive strategy with the implementation of a strategy (growth oriented strategy) which is a very favorable situation with the implementation of marketing mix policies. because it is in the area of strength and opportunity. Aggressive must be done as much as possible, in order to be able to increase growth and achieve maximum progress and the need to keep abreast of technological developments so that they can compete in the midst of the times. Keywords : Marketing Mix, Thrift